Sustainable production of natural dyes for textile product via SUBMEX - Mimi Sakinah, A. M. (Pejabat Naib Canselor, 2009)
A novel submerged membrane extractor (SUBMEX) system is developed in order to extract the natural colourants from ‘green’ resources (pitaya fruit waste, senduduk and turmeric). The membrane is assembled in a modular form with appropriate membrane surface area.